Homegarden Agroforestry in Ethiopia- A Review - Kefale, Biruk (International Journal of Bio-resource and Stress Management, 2020)
Agroforestry is an ancient practice and also the farmers are too much familiarized with it in Ethiopia. All homegardens contain some sort of food crops and many trees produce fruits or other forms of food which shows that the most important function of homegardens is food production.Home garden is an integrated system that comprises different things in its small area. Home gardens have been identified as the oldest land use activity. In general terms, all homegardens consist of three main layers; of these herbaceous layers near the ground, a tree layer at upper levels, and intermediate layers in between. The compositions of crops grown in homegardens can be grouped based on function as ornamental, fruits, food crops, vegetables, medicinal, spices and fodder, building materials and fuel woods. Traditional socio-cultural and ecological knowledge often permits the farmer to decide the species choice and the spatial and time sequence for growing these species. Homegardens are perceived to be highly sustainable in both biophysical and socioeconomic terms.Homegardensmay be characterized by diverse composition, complexstructure and multiple functions.Homegardens are realized as an important self-sustaining agroecosystem with the dual function of production and on farm conservation of the agrobiodiversity.The perceived threat of genetic erosion to plant resources for food and agriculture could be arrested by ensuring the worth of homegardens, because they ensure conservation of useful plants through continued use . Ethiopian homegardens are unique in their architecture, crop mix and the key (dominant) species.